2013
DOI: 10.1371/journal.pone.0067262
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Spontaneous Neural Activity in Obsessive-Compulsive Disorder: A Resting-State Functional Magnetic Resonance Imaging Study

Abstract: Neuroimaging studies of obsessive-compulsive disorder have found abnormalities in orbitofronto-striato-thalamic circuitry, including the orbitofrontal cortex, anterior cingulate cortex, caudate, and thalamus, but few studies have explored abnormal intrinsic or spontaneous brain activity in the resting state. We investigated both intra- and inter-regional synchronized activity in twenty patients with obsessive-compulsive disorder and 20 healthy controls using resting-state functional magnetic resonance imaging.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 55 publications
7
37
1
Order By: Relevance
“…Decreased gray matter volumes in the orbitofrontal cortex, dorsolateral prefrontal cortex and anterior cingulate cortex, and increased gray matter volumes in the putamen, caudate and thalamus have been reported in previous OCD studies [3,4]. Local abnormal regional functional characteristics in the orbitofrontal cortex, anterior cingulate cortex, caudate and thalamus have been detected in OCD patients [5][6][7]. Moreover, changes in the resting-state functional connectivity (RSFC) among these brain regions have also been…”
Section: Introductionmentioning
confidence: 65%
“…Decreased gray matter volumes in the orbitofrontal cortex, dorsolateral prefrontal cortex and anterior cingulate cortex, and increased gray matter volumes in the putamen, caudate and thalamus have been reported in previous OCD studies [3,4]. Local abnormal regional functional characteristics in the orbitofrontal cortex, anterior cingulate cortex, caudate and thalamus have been detected in OCD patients [5][6][7]. Moreover, changes in the resting-state functional connectivity (RSFC) among these brain regions have also been…”
Section: Introductionmentioning
confidence: 65%
“…These findings are consistent with an overactive error control system in OCD subserving suppression of prepotent responses during decision-making. Several studies of FC connectivity confirmed alteration in the fronto-striato-thalamo-cortical (i.e., [199][200][201][202][203][204][205][206][207]). The dysregulation of the fronto-striato-thalamo-cortical circuit may be one of the major findings, which can help to differentiate the two disorders, as the presence of an increased WM integrity during in pediatric and adolescent patients affected by OCD.…”
Section: Developmental Perspectivementioning
confidence: 95%
“…The cerebellum seems to be less activated in patients with OCD [7,8], but there is a lack of studies exploring the clinical implications of this phenomenon. Several studies & Arnaud Tessier…”
Section: Dear Sirsmentioning
confidence: 99%
“…The cerebellum seems to be less activated in patients with OCD [7,8], but there is a lack of studies exploring the clinical implications of this phenomenon. Several studies have investigated the potential role of cerebellar infarcts in the occurrence of post-stroke behavior changes [9,10].…”
Section: Dear Sirsmentioning
confidence: 99%
See 1 more Smart Citation